Challenges in orchard management for almond and pistachio - Lansari A. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
Almond and pistachio are the two main fruit nuts in the Mediterranean region and the USA. According to acreage importance and history in producing countries, USA is considered the latest country that introduced these two crops, starting by the beginning of the 20th century. Yet, the country has evolved tremendously in orchard management beside the other factors to assure high production to become the first almond and the second pistachio world producer. Mediterranean countries, where most of the acreage of these two species is located, developed good research and development in orchard management approaches and techniques and reached excellent production and fruit quality levels. However, their advances are uneven, slowed by the historical load of the crop and its management in their respective countries. At present, new issues have raised that will impact the future of orchard management. Per se, water resources shortage and fertilizers use in relation to climatic changes and soil contaminations, pesticides use in relation to environment pollution and health concerns, and the new developing trends such as bio, labeled and natural products. Thus the challenge in orchard management in pistachio and almond is greater since it should in the mean time aim to guarantee good and profitable economical yields and respect all the environmental and climatic changes concern.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)